THE NEED TO PREPARE FUTURE ECONOMISTS, FOCUSED ON INNOVATIVE MODERNIZATION OF THE NATIONAL ECONOMY IN EDUCATION «COLLEGE - UNIVERSITY » - Носач, І. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The article is devoted to the issue of training specialists of economic profile in the education system "College - universities" in the aspect of the modernization of the Ukrainian economy in connection with the entry of Ukraine into the European Union. The differentiation of professionally trained and a competent economist, the role of innovation in training economists, possible changes of the conditions of professional training of economists has training economists-oriented innovative modernization of national economy